Perceptions about prenatal care: views of urban vulnerable groups - Hatcher Barbara; Jackson Velishie; Monroe-Lord Lillie; Rodan Margaret; Richards Leslie; Wingrove Barbara K; Milligan Renee; Harris Cynthia; Henderson Cassandra; Johnson Allan A (BMC, 2002)
Abstract Background In the United States, infant mortality rates remain more than twice as high for African Americans as compared to other racial groups. Lack of adherence to prenatal care schedules in vulnerable, hard to reach, urban, poor women is associated with high infant mortality, particularly for women who abuse substances, are homeless, or live in communities having high poverty and high infant mortality. This issue is of concern to the women, their partners, and members of their communities. Because they are not part of the system, these womens' views are often not included in other studies. Methods This qualitative study used focus groups with four distinct categories of people, to collect observations about prenatal care from various perspectives. The 169 subjects included homeless women; women with current or history of substance abuse; significant others of homeless women; and residents of a community with high infant mortality and poverty indices, and low incidence of adequate prenatal care. A process of coding and recoding using Ethnograph and counting ensured reliability and validity of the process of theme identification. Results Barriers and motivators to prenatal care were identified in focus groups. Pervasive issues identified were drug lifestyle, negative attitudes of health care providers and staff, and non-inclusion of male partners in the prenatal experience. Conclusions Designing prenatal care relevant to vulnerable women in urban communities takes creativity, thoughtfulness, and sensitivity. System changes recommended include increased attention to substance abuse treatment/prenatal care interaction, focus on provider/staff attitudes, and commitment to inclusion of male partners.